Guanylate cyclase-C/cGMP: an emerging pathway in the regulation of visceral pain - Hannig, Gerhard; Tchernychev, Boris; Kurtz, Caroline B.; Bryant, Alexander P.; Currie, Mark G.; Silos-Santiago, Inmaculada (Frontiers in Molecular Neuroscience, 2014)
Activation of guanylate cyclase-C (GC-C) expressed predominantly on intestinal epithelial cells by guanylin, uroguanylin or the closely related GC-C agonist peptide, linaclotide, stimulates generation, and release of cyclic guanosine-3′,5′-monophosphate (cGMP). Evidence that the visceral analgesic effects of linaclotide are mediated by a novel, GC-C-dependent peripheral sensory mechanism was first demonstrated in animal models of visceral pain. Subsequent studies with uroguanylin or linaclotide have confirmed the activation of a GC-C/cGMP pathway leading to increased submucosal cGMP mediated by cGMP efflux pumps, which modulates intestinal nociceptor function resulting in peripheral analgesia. These effects can be reproduced by the addition of exogenous cGMP and support a role for GC-C/cGMP signaling in the regulation of visceral sensation, a physiological function that has not previously been linked to the GC-C/cGMP pathway. Notably, targeting the GC-C/cGMP pathway for treatment of gastrointestinal pain and abdominal sensory symptoms has now been validated in the clinic. In 2012, linaclotide was approved in the United States and European Union for the treatment of adult patients with irritable bowel syndrome with constipation.